3D Printing of Micro‐Architected Al/CuO‐Based Nanothermite for Enhanced Combustion Performance. Issue 12 (15th October 2019) - Mao, Yaofeng; Zhong, Lin; Zhou, Xu; Zheng, Dawei; Zhang, Xingquan; Duan, Tao; Nie, Fude; Gao, Bing; Wang, Dunju
Abstract : The booming development of 3D printing offers unprecedented hope for the construction of functional materials. However, it is still challenging to fabricate nano energetic materials due to the high sensitivity of energetic materials and the difficulty of high loading of materials. Recently, ink‐based direct ink writing (DIW) 3D printing process for the preparation of reactive materials has attracted worldwide attention because of the simplicity in design of micro architecture and the possibility of low‐cost manufacturing. Herein, a novel strategy for printing Al/CuO nanothermite is successfully achieved by DIW 3D printing of nanothermite inks with good rheology shear‐thinning properties using F2311 as a binder. The loading of nanothermite in this ink formula is up to 90 wt.%, and the burning rate can be as high as 352 mm s −1 . This approach provides new routes for achieving the applications in micro energetic device by printing high resolution and precise patterns of nanothermite with enhanced combustion performance. Abstract : This work introduces novel Al/CuO nanothermite that can be achieved in 3D printing approach by preparing hydrothermal inks with good rheology shear‐thinning properties in the presence of F2311 as a binder. The printed micro‐architected patterns with high loading of 75–90 wt.% nanothermite and tunable burning rate ranging from 32 to 352 mm s −1 .